Comparative study of mineral composition of beef steak and pork chops depending on the thermal preparation method. (August 2016) - Goran, Gheorghe Valentin; Tudoreanu, Liliana; Rotaru, Elena; Crivineanu, Victor
Abstract: This study focuses on the effects of three different thermal preparation methods (roasting, boiling, and microwave cooking) on the mineral concentrations of beef and pork, as well as on the comparison of mineral levels between these two types of meat. In this study, raw and cooked beef and pork samples were selected and analyzed by ICP-OES in order to determine mineral concentrations. In general, thermal preparation clearly increased mineral concentrations in cooked samples compared to raw meat. The highest mineral concentration was identified in the roasted samples. Trace element concentrations in beef were significantly higher compared to pork. In pork, Na concentration decreased in all samples, suggesting that Na is lost with water. Zn mean content in cooked beef samples registered significant differences compared to pork cooked samples. The percentage of water loss during the microwave thermal preparation for beef samples was higher than the other two treatments. Highlights: Different thermal transfer cooking types influence the chemical composition of beef and pork. Thermal preparation increases meat minerals concentrations compared to raw meat. The highest mineral concentration is registered in roasted beef and pork samples. The minerals concentrations in beef rib eye steak are significantly higher compared to pork loin. Recommendation for choosing the most effective meat cooking method to maintain or improve its nutritional quality.